2023
DOI: 10.1200/op.22.00718
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparity in the Relationship of Mental and Physical Health With Colorectal Cancer Screening Utilization Among Breast and Prostate Cancer Survivors

Abstract: PURPOSE: We examined colorectal cancer (CRC) screening utilization among non-Hispanic White, non-Hispanic Black (NHB), non-Hispanic other (NHO)/Hispanic cancer survivors. We also determined whether experiencing poor physical and/or mental health affects CRC screening utilization in breast and prostate cancers across different racial/ethnic groups. METHODS: Data from years 2016, 2018, and 2020 of the Behavioral Risk Factor Surveillance System on 3,023 eligible treatment-utilizing cancer survivors with complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Finally, our results showed that cancer survivors who perceived themselves to have fair or poor health or had an additional CC were more likely to experience mild and moderate to severe psychological distress. Prior studies have shown that poorly perceived health and comorbid medical conditions are correlated with experiencing symptoms of psychological distress [20,56,57]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, our results showed that cancer survivors who perceived themselves to have fair or poor health or had an additional CC were more likely to experience mild and moderate to severe psychological distress. Prior studies have shown that poorly perceived health and comorbid medical conditions are correlated with experiencing symptoms of psychological distress [20,56,57]…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerable populations, particularly rural populations, sexual and gender minorities, and minoritized racial and ethnic populations, often face greater challenges navigating cancer survivorship [16,17]. Racial and ethnic minority groups may also experience disparities in cancer survivorship, including differential access to early treatment and quality care, leading to inequalities in physical and mental health outcomes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior study observed that Hispanic survivors were less likely to be screened for CRC [ 13 ]. Factors associated with low screening use include worse quality of life and low income among Hispanic survivors [ 15 ]. Conversely, greater CRC screening use was found when survivors received a survivorship care plan in breast, cervical, colorectal, prostate, melanoma, and other cancers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%